Detection of transformer winding fault using Frequency Response Analysis (FRA) / Nurul Atikah Saeidi - Saeidi, Nurul Atikah (2013)
Transformer is the important equipment in order to step up or step down the current or voltage. Besides that, transformer is specified to withstand the mechanical forces from both transportation and in-service events like faults and lightning. Due to its function, it is a must to take a good care or concern about its condition for long lifetime. In order to avoid it from breakdown or do not function properly, transformer need to be examined. This paper presents a method for detection of the transformer winding fault. Analysis was made on healthy and unhealthy transformer by visualization and cross correlation coefficient using Frequency Response Analysis (FRA). From the shape of waveform and value of cross correlation, the condition of the transformer will be determined. By using MATLAB software, the shape of the waveform based on the given data has been plotted. Also, the value of cross correlation has been obtained by using Microsoft EXCEL.